Kitab Safinah Kalla Saya’lamun dalam Diskursus Khazanah Tafsir Pesantren - Arini Jauharoh; Muhammad Khoirul Anwar (STAI Darul Kamal NW Kembang Kerang, 2025)
This article aims to conduct an analysis of Islamic boarding school tafsir treasures by taking a case study of Safinah Kalla Saya’lamun Fi Tafsir Syaikhina Maimun. In general, this work is part of the Indonesian interpretation. However, so far the mapping of the Tafsir Nusantara typology has not touched on the institutional aspect which is an important locus for the emergence of this work. This article questions the background to the writing of Safinah Kalla Saya'lamun? And in the context of what horizon was the work born? These two questions are the basis for expanding the study of the existence of Islamic boarding school interpretive works. This article used qualitative method with the content analysis. This article concludes, that the book Kalla Saya'lamun was originally the result of the Tafsir Jalalain recitation every Sunday read by Maimoen Zubair (d. 2019). The position of the writer who was a student at that time felt the importance of recording the teacher's ideas. However, in fact, the author’s role is not only to explain Zubair's ideas, but also to explore and compare with the views of other commentators. So that it is able to present a literary interpretation of the Al-Qur'an that is not only one way, but presents a rich variety of views using simplistic methods, in addition to presenting ideas that are unique to the locality of the Islamic boarding school. In this case, the interpreter links the meaning of the verse to the current social context or local historical facts. Based on the findings of this work, this research proves that the dynamics of interpretive studies in Islamic boarding schools continue to grow.